Saturday, 16 JUNE 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.1906
|View full text |Cite
|
Sign up to set email alerts
|

SAT0350 Content and face validity and feasibility of five candidate instruments for psoriatic arthritis randomised controlled trials: results from the psa omeract core set workshop at the grappa 2017 annual meeting

Abstract: BackgroundThe Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA) – Outcome Measures in Rheumatology (OMERACT) Psoriatic Arthritis (PsA) Core Set working group is developing a core instrument set to guide selection of outcome measures (instruments) for PsA randomised controlled trials (RCTs) and longitudinal observational studies (LOS). Candidate instrument measurement properties are being appraised in systematic literature reviews by working group members.ObjectivesAppraise the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Domain match and feasibility for the SJC66/TJC68 were addressed at GRAPPA 2017 in a breakout group discussion, and following the meeting, among working group members using a Web-based survey. During the GRAPPA meeting, content validity and feasibility were addressed within a small group with clinicians, 2 patients, and a patient advocate; the voting sheets were completed by 22 people 12 . There was consensus (20/22, 91%) among the group that the SJC66/TJC68 was a match for the MSK disease activity/peripheral arthritis domain and that there was adequacy of content and no redundancies.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Domain match and feasibility for the SJC66/TJC68 were addressed at GRAPPA 2017 in a breakout group discussion, and following the meeting, among working group members using a Web-based survey. During the GRAPPA meeting, content validity and feasibility were addressed within a small group with clinicians, 2 patients, and a patient advocate; the voting sheets were completed by 22 people 12 . There was consensus (20/22, 91%) among the group that the SJC66/TJC68 was a match for the MSK disease activity/peripheral arthritis domain and that there was adequacy of content and no redundancies.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Second, during the GRAPPA 2017 annual meeting COMPACT workshop, one breakout group was dedicated to PsAID12. Facilitators provided the HRQOL domain description, the PsAID12 questionnaire and scoring method; participants then anonymously completed each item of the OMERACT domain match and feasibility questionnaires (11). Third, the working group voted on domain match and feasibility.…”
Section: Domain Match and Feasibilitymentioning
confidence: 99%
“…There was unanimous green vote for PsAID12 feasibility. At the GRAPPA 2017 annual meeting 24 stakeholders voted majority amber for PsAID12 domain match, and majority green for feasibility (11). Twenty-two working group members voted: 17 (82%) green for domain match and 20 (91%) green for feasibility; the rest of the working group votes were amber.…”
Section: Domain Match and Feasibilitymentioning
confidence: 99%
“…The PsAID12 content validity (domain match and feasibility) were assessed in a face-to-face meeting with 12 PsA PRPs, and a multistakeholder breakout group at the GRAPPA PsA core instrument set workshop. 17 In the face-to-face meeting and breakout group, facilitators provided the HRQoL domain description, the PsAID12 questionnaire, and scoring method; participants then anonymously completed each item of the OMERACT domain match and feasibility questionnaires. 13 A working group vote on domain match was also collected, with 22 working group members voting (50% rheumatologists, 23% patients, 13.5% industry, and 4.5% each dermatologists/ trainees/methodologists).…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…Four studies evaluated feasibility of PsAID12 17,20,24,26 and reported high feasibility. Two studies evaluated completion rate and demonstrated !99% completion rate for a paperbased questionnaire.…”
Section: Feasibilitymentioning
confidence: 99%